Treatment of pig farm wastewater by aquatic macrophytes - Diana, Menau Jantan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Piggery wastewater is one of the main sources of water pollution in Sarawak. The present study looks on the ability of two aquatic macrophytes, Ipomoea aqualica and Limnocharis jlava in improving the water quality of the pig fann wastewater. The study were carried out by setting up 14 day batch process where 9 tanks were set up including the controls. The pig farm wastewater was diluted to 1:7 and the parameters evaluated for the pig farm wastewater were total nitrogen, total phosphorus, ammonia-nitrogen, nitrate, reactive phosphorus and chemical oxygen demand whereas the plant tissue were evaluated for total nitrogen and total phosphorus content intially and finally. The Ipomoea aqualica system had shown the highest percent of reduction for total phoshorus and ammonia nitrogen whereas system had shown the highest percent of reduction for chemical oxygen demand and reactive phosphorus. The highest total nitrogen reduction was in the control system. The total nitrogen increment was higher in Limnocharis jlava system but the plant uptake in Ipomoea aqualica system was higher whereas the total phosphorus content, Limnocharis jlava system had higher for both increment and plant uptake. In conclusion, these two aquatic plants have the potential to treat the pig farm wastewater.